A Cross-sectional Study of Community Awareness in Al-Tal District, Syria, about the Random Use of Antibiotics - Alajlani, Muaaz (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2023)
Background: An antibiotic is a type of antimicrobial substance active against bacteria. It is the most important type of antibacterial agent for fighting bacterial infections. Aims: The study aimed to identify the degree of awareness about the dangers of misuse of antibiotics, and to find out the differences about the degree of their knowledge of the dangers of using antibiotics according to the variables (Gender – age – level of education – place of residence). Materials and Methods: This study was conducted through a questionnaire prepared by the researcher consisting of (13) items in addition to some personal information (gender – age – educational level – place of residence), and the informed consent was taken from all (166) study participants. Results: There are no differences in the degree of knowledge of the risks of using antibiotics due to the sex variable, and there are differences between the estimates of the study sample in the degree of knowledge of the risks of using antibiotics. The category (25–39) was the most knowledgeable, and there were differences between the estimates of the study sample members due to the variable of place of residence due to the remote areas. Conclusion: The degree of knowledge of the risks of using antibiotics was low, as the majority of individuals (57%) had followed the advice of someone other than a doctor or used an old prescription before taking an antibiotic. These results clearly indicate the extent to which laws controlling the sale of antibiotics in pharmacies in the Syrian Arab Republic.